PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN PJOK MATERI PERMAINAN BOLA KECIL - Nurul Yaqin (Universitas Tribhuwana Tunggadewi, 2022)
The purpose of this study was to improve student learning outcomes on small ball game material in PJOK through a direct learning model. The subjects in this study were 32 grade VII students of SMPN 45 Surabaya for the 2022-2023 school year. The research used was classroom action research in two cycles with two meetings consisting of four stages, namely planning, implementation, observation, and reflection, using descriptive analysis and student learning outcomes tests. The results showed that the application of the direct learning model can improve student learning outcomes where in cycle I, the completeness of student learning outcomes reached 78% with an average of 76.2, while completeness in cycle II increased to 93 with an average of 88.4. Based on these results, it can be concluded that the application of the direct learning model can actually improve student learning outcomes in learning PJOK small ball game material.